887PUrine extracellular vesicle GATA2 mRNA alone and in a multigene test predicts initial prostate biopsy result. (1st October 2019) - Woo, J; Santasusagna, S; Banks, J; Dominguez-Andres, A; Yadav, K; Pippa, R; Carceles-Cordon, M; Lallas, C D; Luyao, G; Rodriguez-Bravo, V; Tewari, A; Pastor-Lopez, S; et al.
Abstract: Background: Prostate specific antigen (PSA) detection in blood is widely used to screen for prostate cancer (PCa). However, PSA has limited utility in discriminating high risk tumors (Gleason score≥7) from indolent-low risk tumors, which leads to unnecessary biopsies and highlights the need to identify better biomarkers for the detection of clinically significant PCa. GATA2 is a pioneer transcription factors which expression is increased in high-risk prostate cancer (PCa), but its utility in discriminating for PCa remains untested. Methods: To determine whether extracellular vesicle (EV) GATA2 mRNA provides clinically relevant information to distinguish PCa, we prospectively analyzed non-digital rectal exam (DRE) urine EV GATA2 mRNA levels from 165 males with suspicion of PCa prior to biopsy and correlated GATA2 levels alone and combined in a multigene (PCA3 and TMPRSS2) EV mRNA assay to biopsy result. Results: Prostate origin of GATA2 mRNA detected in urine EVs was confirmed by observing that GATA2 mRNA levels significantly dropped after prostatectomy (p < 0.05) and positively correlated to PCa tissue GATA2 mRNA levels. GATA2 increased in biopsy-positive PCa patients (p < 0.0001) and high-grade disease (p < 0.01). Multivariable analysis showed that GATA2 is an independent predictive factor of any cancer and high-grade PCa. GATA2 alone and combined in a multigene test with PCA3 and TMPRSS2-ERG (GAPT-E) improved discrimination of any cancer (GAPT-E1) and high-grade cancer (GAPT-E2): standard of care (SOC) area under the curve (AUC) of 0.62 and 0.65, SOC plus GATA2 AUC of 0.68 and 0.69, and SOC plus GAPT-E (1-2) AUC of 0.75 and 0.75, respectively. A GAPT-E1 cut-point of 57 would avoid 25.6% of unnecessary prostate biopsies and 13.7% of total biopsies with NPV 50% and missing 9% of PCa. Limitations include lack of PCa volume and imaging assessment of the cohort. Conclusions: Non-DRE urine EV GATA2 mRNA alone and in combination with other urine EV biomarkers in men with suspicion of PCa provides useful information to distinguish any cancer and high-risk PCa and may reduce the number of biopsies. Legal entity responsible for the study: The authors. Funding: NCI/NIH. Disclosure: K. Yadav: Full / Part-time employment: SEMA4. A. Tewari: Research grant / Funding (self): Boston Scientific Corporation, Medtronic, Inc. (10/15/2013); Licensing / Royalties: DNA Based Bicistronic Vectors with Inducible and Constitutive Promoters - ID#: 160608, High Intensity Focus Ultrasound and CPG-Brachyury-siRNA for Treatment of Prostate Cancer - ID# 160403, Patent for a Catheterless Device and Approach, Uretheral Catheter; Leadership role: Global Prostate Cancer Research Foundation, Kalyani Prostate Cancer Institute, Peter Georgescu Foundation Award, Promaxo; Advisory / Consultancy: Roivant, Siemens. W.K. Kelly: Advisory / Consultancy: Sanofi, Foundation Medicine; Travel / Accommodation / Expenses: Janssen Oncology; Honoraria (self): Janssen Oncology, Constellation Pharmaceuticals; Research grant / Funding (institution): Sanofi, Novartis, Janssen Oncology, Bayer, Exelixis, Seattle Genetics, Endocyte. B.E. Leiby: Advisory / Consultancy: Bayer. L. Gomella: Honoraria (self), Advisory / Consultancy: Astellas/Janssen/Mdx Health/Strand; Research grant / Funding (self): FKD; Licensing / Royalties: Jefferson IP. All other authors have declared no conflicts of interest.